The last deglaciation and its geomorphological imprint at Elgåhogna, Femunden area, SE Norway - Weber, Paul (2014)
The core area of the last Scandinavian Ice Sheet (SIS) in south-central Scandinavia is believed to have had a cold-based glacier thermal regime, preserving landforms created during earlier glaciations, interstadials and even preglacial epochs. These relict features are often juxtaposed with the sparse, meltwater-dominated landform record of the last deglaciation and, as a result, complicate reconstructions of the deglacial history of the last SIS in this region. Here, geomorphological mapping supplemented with sedimentary logging is employed to reconstruct the last deglaciation at Elgåhogna in the Femundsmarka Mountains of southeastern Norway, an area that was located right in the center of the last SIS and its supposed cold-based interior. A literature review of the last deglaciation in south-central Scandinavia places the results of the mapping in a broader, regional perspective. Ice sheet decay at Elgåhogna took place by vertical downwasting such that the summit areas of the massif emerged first from the ice sheet surface as nunataks, thereby splitting the remaining ice around the mountain into two major fragments. Each fragment melted at distinctly different rates. The ice sheet remnant on the eastern mountainside decayed slowly and, after constructing a prominent glaciolacustrine delta, eventually became buried under supraglacial debris at the foot of Elgåhogna. Conversely, the ice on the western side of mountain thinned rapidly into the valley, forming eskers and, on the other hand, lateral meltwater channels that mark the progressive lowering of the ice sheet surface. Such a complex and non-uniform deglaciation pattern is consistent with the results of a comprehensive literature review which found that ice sheet fragmentation and the topographic confinement of ice to major valleys and upland depressions during downwasting led to a highly differential retreat behavior of the last SIS in south-central Scandinavia. While there is no evidence that the last SIS at Elgåhogna was cold-based, there is ample evidence for a stable warm-based glacier thermal regime. Eskers were deposited in subglacial conduits and demonstrate that the last SIS around the mountain exhibited a highly integrated subglacial drainage system, a feature that is assumed to be absent in cold-based glaciers. Traces of subglacial erosion are widespread, although the degree of erosion is limited at higher elevations due to low horizontal flow rates and low erosion rates in ice divide areas. Lateral meltwater channels were formed only in response to occasional winter cold wave chilling. This tentatively suggests that the basal thermal regime in the center of the last SIS varied more than has been previously thought.